Pengaruh Visual Merchandising terhadap Perilaku Pembelian Impulsif Konsumen Ritel di Bojonegoro - Irnawati, Dwi; Kustaji; Saputra, Muhammad Yoga Aditya (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Visual merchandising has long been considered an essential marketing tool in the retail world. In this study, the researcher wanted to find out how much influence visual structuring had on customers' impulse buying behavior. This study takes Najah Fashion as a case study and involves customers as a sample. The methods used are descriptive to help understand this concept more deeply, as well as to provide information that can help the company make decisions. Data were collected using a structured questionnaire and analyzed to determine the effect of visual merchandising on impulse buying. The research sample consisted of 100 purposively selected respondents in Bojonegoro. The study found that impulse buying significantly contributed to sales across various product types, with 46% of respondents stating that they had made unplanned purchases after being exposed to certain visual elements. Among the four visual merchandising factors examined, promotional signage at the store entrance proved to have the greatest influence on impulse buying behavior, with a regression coefficient of β = 0.956 and a significance level of p < 0.05. This indicates that promotions strategically displayed at the entrance area have a strong appeal in encouraging consumers to make spontaneous purchases.